2018
DOI: 10.1007/s10995-018-2639-2
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient status of populations and preventive nutrition interventions in South East Asia

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Overall, protein intake was sufficient, except that there were relatively high proportions of insufficient intake among older adult women (31.1%), and pregnant women (31.9%) and lactating women (41.1%). Precisely during these life stages, getting enough protein requires more attention since it is required for optimal maternal and child health and for maintenance of muscle function in the elderly [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, protein intake was sufficient, except that there were relatively high proportions of insufficient intake among older adult women (31.1%), and pregnant women (31.9%) and lactating women (41.1%). Precisely during these life stages, getting enough protein requires more attention since it is required for optimal maternal and child health and for maintenance of muscle function in the elderly [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Bangladesh National micronutrient survey 2011, among children aged 6-60 months, 33% were anemic, 3.9% had iron deficiency, 20.5% had vitamin A deficiency, and 44.6% had zinc deficiency at the national level [33,34]. A recent review of the micronutrient status of under-five year South Asian children also reported similar burdens of anemia and iron, zinc, and vitamin A deficiencies [35].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded a need for multileveled interventions that address both proximate and distal factors underlying child malnutrition, and also advocated for more comprehensive implementation science studies examining scale-up efforts (Cordon et al 2019). Similarly, Roos et al (2018) examined population-based nutrition interventions in South East Asia. Researchers cited lack of routine data collection and monitoring as a major barrier to program scale up in countries such as Cambodia, Indonesia, and Vietnam (Roos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Roos et al (2018) examined population-based nutrition interventions in South East Asia. Researchers cited lack of routine data collection and monitoring as a major barrier to program scale up in countries such as Cambodia, Indonesia, and Vietnam (Roos et al 2018). Moreover, Kim et al (2017) reported intersectoral coordination as a major facilitator in scaling up nutrition interventions in India, where governments, policy makers, and stakeholders have a shared understanding of overall program goals and priority actions (Kim et al 2017).…”
Section: Introductionmentioning
confidence: 99%